Migrant-led diversification and differential inclusion in arrival cities across Asia and the Pacific - Ye, Junjia (2023)
The closely related processes of migration and diversification call for greater scrutiny of how contemporary arrival cities incorporate increasingly diverse groups of newcomers through practices and processes of differential inclusion. This special issue highlights arrival cities in the Asia-Pacific region, attending to how they are being transformed by the wide-ranging temporal and spatial dimensions of migrant-driven diversification. Rather than begin with how coexistence in the context of diversification ought to be, the collection of papers included here builds inter-references through contexts that are, ultimately, non-universal. In so doing, this special issue responds to recent calls by social scientists to extend our frames of reference beyond the dominant centres of knowledge production in Europe and North America in understanding the links between migration and urban diversity. The papers included here focus on arrival cities and urban places in Hong Kong, the Philippines, Singapore, Malaysia, Japan, Australia and New Zealand as an exercise in open-ended imagination, advancing the conversation on urban diversification in the age of global migration. We organise these forms of urban change and migration-driven differentiation along four key themes of temporalities, spatialities, intermediaries and norms that emerged from the collection of papers. Using these four conceptual themes, modes of differential inclusion function as tools of discipline and governance at one level, and are mobilised to subvert and negotiate power relations at another. As refracted through these four axes of analysis, differential inclusion draws our attention to the multiscalar and multi-actor politics of diversification.